Analisis Kadar Rhodamin B pada Terasi yang Diperjualbelikan di Pasar Belik Kabupaten Pemalang - Oden Krisyan; Retno Sulistiyowati; Kurniawan Kurniawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Terasi is a cooking spice made from fermented shrimp and is often found in the market. It is relatively affordable and easy to find, so people flavor it as a flavor enhancer for their food. The abuse of Rhodamine B as a Food Additive (BTP) in terasi is often done by the producers. This study aimed to analyze the Rhodamine B content in the terasi sold at the Pasar Belik, Pemalang Regency. The study was conducted in a descriptive observational manner where the sample was analyzed qualitatively, and if the result were positive, it would be followed by quantitative. The study was conducted in December 2020. Rhodamine B content in terasi was analyzed by univariate test. Qualitative analysis was carried out by chemical methods using 10% NaOH, Petroleum Ether, and 10% HCl. The qualitative analysis of 7 samples of shrimp paste sold at the Belik Market in Pemalang Regency were all negative and did not contain Rhodamine B. Shrimp samples that were bought and sold at the Pasar Belik in Pemalang Regency showed that they were free from Rhodamine B.